Thiopurine methyltransferase genotype and activity cannot predict outcomes of azathioprine maintenance therapy for antineutrophil cytoplasmic antibody associated vasculitis: A retrospective cohort study. - Arno C Hessels; Abraham Rutgers; Jan Stephan F Sanders; Coen A Stegeman (PLoS ONE, 2018)
Azathioprine is a widely used immunosuppressive drug. Genetic polymorphisms and activity of the enzyme thiopurine methyltransferase (TPMT) have been associated with azathioprine efficacy and toxicity in several populations. We investigated whether these associations also exist for ANCA associated vasculitis (AAV) patients, who receive azathioprine maintenance therapy after remission induction with cyclophosphamide.207 AAV patients treated with cyclophosphamide induction and azathioprine maintenance therapy were included and followed for 60 months. TPMT genotype and tertiles of TPMT activity were compared to relapse free survival and occurrence of adverse events, particularly leukopenia. Multivariable regression was performed to account for confounders.In univariable analysis, relapse free survival was not significantly associated with TPMT genotype (P = 0.41) or TPMT activity (P = 0.07), although it tended to be longer in lower tertiles of TPMT activity. There was no significant association of TPMT genotype and activity with occurrence of any adverse event. In multiple regression, leukocyte counts at the end of cyclophosphamide induction were related to risk of leukopenia during azathioprine therapy [P<0.001; OR 0.54 (95% CI 0.43-0.68)] and risk of relapse during follow-up [P = 0.001; HR 1.17 (95% CI 1.07-1.29)] irrespective of TMPT genotype or activity.TPMT genotype and activity were not independent predictors of relapse, and could not predict leukopenia or other adverse effects from azathioprine. Leukocyte counts after cyclophosphamide induction were related to both outcomes, implying a greater influence of cyclophosphamide response compared to azathioprine and TPMT in AAV patients.